Bone morphogenetic proteins 2, 6, and 9 differentially regulate the osteogenic differentiation of immortalized preodontoblasts - Cao,Yuying (2020)
Our study attempted to compare the efficacies of bone morphogenetic protein (BMP) 2, 6, and 9 in inducing osteogenic differentiation of preodontoblasts (PDBs). We immortalized PDBs by introducing a reversible SV40 T antigen-based immortalization system. Cell proliferation capability was examined by the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide assay. The effects of BMP2, 6, and 9 on the osteogenic differentiation of immortalized preodontoblasts (iPDBs) were measured by alkaline phosphatase (ALP) activity assays and alizarin red S staining. The expression of osteogenic markers was evaluated by semiquantitative real-time polymerase chain reaction analysis. To assess ectopic bone formation, rat-derived iPDBs were transfected in culture with adenoviral vectors designated Ad-BMP2, 6, and 9 and subcutaneously or intramuscularly injected into mice. Several BMPs retained endogenous expression in PDBs and regulated the mRNA expression of mineralized tissue-associated proteins. ALP activity and mineralized nodule formation were significantly increased in the Ad-BMP9-transfected group relative to the control group. In addition, the most significant hard tissue formation was in this group. The results indicated that BMP signaling was involved in the osteogenic differentiation of iPDBs. BMP9 could be an efficacious accelerant of the osteogenic differentiation of iPDBs.